Beyond the Spanish State - Jones, R. author. aut Link
XV, 229 p.
Keywords: Beyond the Spanish State is a well researched and accessibly written study of EU policy-making in Spain. From the fishermen in Andalusia fighting to protect their quotas, to regional governments demanding a greater say in EU Structural Funds, the book represents a masterful effort to delve deeper into the dynamic relations between central government and other actors in the domestic arena. Conclusions most directly pertain to the case of Spain but, nonetheless, provide an insight into the broader EU framework.